Back Cover: Synthesis, Structure and Gas‐Phase Reactivity of a Silver Hydride Complex [Ag3{(PPh2)2CH2}3(μ3‐H)(μ3‐Cl)]BF4 (Angew. Chem. Int. Ed. 32/2013). Issue 32 (26th June 2013) - Zavras, Athanasios; Khairallah, George N.; Connell, Timothy U.; White, Jonathan M.; Edwards, Alison J.; Donnelly, Paul S.; O'Hair, Richard A. J.
<x xml:space="preserve">Abstract</x> Mass Spectrometry Man saves the day! Traveling from his home on planet Gas Phase, he used his ESI‐MS powers to provide G. N. Khairallah, P. S. Donnelly, R. A. J. O'Hair, and co‐workers with vital information for their Communication on page 8391 ff. MS Man's powers revealed the formation of novel silver hydride nanocluster cations in silver salts reduced by sodium borohydride in the presence of a bis(phosphino) ligand, and led the way to the condensed‐phase synthesis, isolation, and characterization of [Ag3{(Ph2P)2CH2}3(μ3‐H)(μ3‐Cl)]BF4⋅0.5 CHCl3.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>